Introduction of taxanometry to evaluate a new Davaineidae tapeworm Cotugnia tuljapurensis Sp. Nov. from Colmbia livia from Osmanabad district (M.S.), India - Jaywant S. Dhole2, *Karmveer N. Kadam1, (International Multidisciplinary Research Journal, 2011)
The present communication deals with a new Davaineidaen tapeworm belonging to the genus Cotugnia Viz, Cotugnia tuljapurensis Sp. Nov. has been described from the intestine of Columba livia, at Tuljapur, Osmanabad district, (M.S.) of India and compared with the existing species. Due to possession scale squarish, mature segment squarish in shape testes 260 in number, ovary horse shoe shaped, longitudinal excretory canals are medium it has been separated from all the known species.Ã‚Â 